2016
DOI: 10.1016/j.jneuroim.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microglia activation after hypoxia–ischemia results in age-dependent improvements in neurologic injury

Abstract: We previously found increased microglial proliferation and pro-inflammatory cytokine release in infant mice compared to juvenile mice after hypoxia-ischemia (HI). The aim of the current study was to assess for differences in the effect of microglial suppression on HI-induced brain injury in infant and juvenile mice. HI was induced in neonatal (P9) and juvenile (P30) mice and minocycline or vehicle was administered at 2 hours and 24 hours post-HI. P9 minocycline-treated mice demonstrated early but transient imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…Consistent with these observations, minocycline did not affect motor deficits in brain-injured adult mice (Bye et al, 2007) or spatial learning and memory following HI in neonatal mice (Cikla et al, 2016) and TBI in adult rats (Kelso et al, 2011). This lack of sustained effect may be due to the fact that the half-life of minocycline in rodents is rather short (2–3 hours) (Andes and Craig, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Consistent with these observations, minocycline did not affect motor deficits in brain-injured adult mice (Bye et al, 2007) or spatial learning and memory following HI in neonatal mice (Cikla et al, 2016) and TBI in adult rats (Kelso et al, 2011). This lack of sustained effect may be due to the fact that the half-life of minocycline in rodents is rather short (2–3 hours) (Andes and Craig, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…Short-term administration of minocycline (similar to the paradigm used in study 1) has been found effective in decreasing microglial activation following neonatal hypoxic ischemia (Cai et al, 2006; Cikla et al, 2016; Fan et al, 2006; Lechpammer et al, 2008), pediatric cardiac arrest (Tang et al, 2010), neonatal repetitive TBI (Hanlon et al, 2016), and adult TBI (Bye et al, 2007; Homsi et al, 2010; Siopi et al, 2011). The reduction in activated microglia was accompanied by an attenuation of neuronal damage (Cikla et al, 2016), a decrease in asphyxia-induced neurodegeneration (Tang et al, 2010), and a reduction of lesion volume following TBI (Homsi et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the localization of the injury depends on the gestational age and the duration and the severity of the insult, hippocampus is one of the most commonly effected regions in the CNS after term neonatal HI, and increased hippocampal astrogliosis has been confirmed by up-regulation of the Glial Fibrillary Acidic Protein (GFAP) 3 d after the neonatal HI 7,10,12,13 . Sex differences in astrocyte function were shown in both neonates and adult rodents after cerebral ischemia 14,15 .…”
Section: Introductionmentioning
confidence: 99%